Diversity Is What You Want It to Be - Unzueta, Miguel M.; Knowles, Eric D.; Ho, Geoffrey C. (Psychological Science, 2012)
We propose that diversity is a malleable concept capable of being used either to attenuate or to enhance racial inequality. The research reported here suggests that when people are exposed to ambiguous information concerning an organization’s diversity, they construe diversity in a manner consistent with their social-dominance motives. Specifically, anti-egalitarian individuals broaden their construal of diversity to include nonracial (i.e., occupational) heterogeneity when an organization’s racial heterogeneity is low. By contrast, egalitarian individuals broaden their construal of diversity to include nonracial heterogeneity when an organization’s racial heterogeneity is high. The inclusion of occupational heterogeneity in perceptions of diversity allows people across the spectrum of social-dominance orientation to justify their support for or opposition to hierarchy-attenuating affirmative-action policies. Our findings suggest that diversity may not have a fixed meaning and that, without a specific delineation of what the concept means in particular contexts, people may construe diversity in a manner consistent with their social motivations.